MANAJEMEN STRATEGI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) PROVINSI RIAU DALAM UPAYA MENINGKATKAN INVESTASI DI PROVINSI RIAU TAHUN 2023-2024 - Ramadhani, Erry Oktaviani; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study aims to determine the strategic management of the Riau Province Investment and One-Stop Integrated Services Agency (DPMPTSP) in increasing investment in Riau Province in 2023-2024. The research problem is motivated by the suboptimal realization of investment and the uneven distribution of investment, despite investment achievements showing a fluctuating trend over the past four years. This study uses a qualitative approach with descriptive methods. Data were collected through interviews, documentation, and literature review, then analyzed using Wheelen and Hunger's strategic management theory, which includes environmental analysis, strategy formulation, strategy implementation, and evaluation and control. The results show that during the environmental analysis stage, the DPMPTSP has identified investment opportunities and challenges, but the integration of regional potential data is still suboptimal. The strategic management of the Riau Province DPMPTSP in increasing investment has been quite effective, but requires strengthening in aspects of promotion, data integration, and institutional capacity building to achieve equitable and sustainable investment. Keywords: Strategic Management, Investment, One-Stop Integrated Services, Public Services